An exploratory study on the experiences of female youth victims of crime during load shedding in Site C, Khayelitsha - Dike, Megan (Department of Public Law, 2025)
Load shedding has become a common problem in South Africa, resulting in daily disruptions affecting every sector of life. Load shedding is a planned and temporary disruption of energy supply to specific areas. The present study explored the experiences of crime of female youth during load shedding at night in Site C, Khayelitsha. While there is extensive literature on the impact of load shedding on crime, no attention has been given to its impact on crime against female youth in Site C, Khayelitsha. The study fills this gap in the existing literature. Although males can experience crime too, the focus of this study is on the experiences of the female youth. Using a qualitative research approach, semi-structured interviews were conducted with 15 female youth residents of Site C, of which 8 out of the 15 participants directly experienced crime during load shedding and the other 7 participants had not directly experienced crime, but were witnesses of crime during load shedding. The findings of this study indicate that load shedding is associated with higher levels of robberies, with house robbery being the most common crime during load shedding. Furthermore, the research underscores the role of environmental factors in shaping crime opportunities and highlights the disproportionate impact load shedding has on the female youth. The study also emphasizes the urgent need for targeted interventions to protect vulnerable groups during load shedding.